2019
DOI: 10.1093/ptj/pzz182
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Shoulder Impingement Syndrome and Thoracic Posture

Abstract: Background Shoulder impingement syndrome (SIS) is the most common form of shoulder pain and a persistent musculoskeletal problem. Conservative and invasive treatments, aimed at the shoulder joint, have had limited success. Research suggests shoulder function is related to thoracic posture, but it is unknown whether thoracic posture is associated with SIS. Objective The objective of this study was to investigate whether there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 47 publications
0
13
0
2
Order By: Relevance
“…This study was part of a cross-sectional study investigating the possible relationship between thoracic posture (measured from a single lateral radiograph) and SIS [ 31 ]. Participants recruited ( n = 78) were between 40 and 80 years of age, given the increase in prevalence of SIS from the age of forty [ 10 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was part of a cross-sectional study investigating the possible relationship between thoracic posture (measured from a single lateral radiograph) and SIS [ 31 ]. Participants recruited ( n = 78) were between 40 and 80 years of age, given the increase in prevalence of SIS from the age of forty [ 10 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The sample size of this study was determined as the number of participants required for the case-control study investigating differences in posture between individuals with and without SIS [ 31 ]. A 5 degree difference in modified Cobb angle between groups (SIS and healthy controls), a standard deviation of 10 degrees (estimated from Katzman et al (2013) and Fon et al (1980) [ 33 , 34 ]) established 34 participants per group to achieve 80% power with a 5% level of significance.…”
Section: Methodsmentioning
confidence: 99%
“…The results of this study appeals to the fact that shoulder position is not a key factor or a clear contributor to shoulder pain [ 11 , 22 ]. These results are in agreement with the findings of Ozunlu et al [ 23 ] and Ribeiro et al [ 23 ] Ozunlu et al [ 23 ] showed that asymmetric scapular posture in volleyball players might be normal and not necessarily related to injury and Ribeiro A et al [ 23 ] reported that scapular asymmetry may be normal and it should not be automatically considered as a pathological sign in throwing athletes.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to some postural alterations such as an antepulsion of the shoulder can alter the mechanosensitivity of different tissues, thus decreasing their tolerance to mechanical stress even if it does not provoke a nociceptive response [ 10 ]. A recent study adds data on this association by concluding that individuals with shoulder impingement syndrome had a greater thoracic kyphosis and less extension movement than age- and gender-matched healthy controls [ 11 ]. For all these reasons, more studies are needed in the sports population to observe whether these types of associations or relationships exist and what clinical implications they may have.…”
Section: Introductionmentioning
confidence: 99%
“…According to the statistical results of relevant clinical research data, the rotator cuff injury accounts for about 16.9% to 40.3% of the shoulder joint's various related diseases. Attention to rotator cuff injuries and early treatment is of great significance in preventing rotator cuff joint disease [ 5 ]. Through timely and correct diagnosis and early treatment, other joint and severe diseases caused by reduced shoulder joint movement function can be reduced.…”
Section: Discussionmentioning
confidence: 99%